On the principles of classification of arable soils in Russia - M. S. Simakova (Бюллетень Почвенного института им. В.В. Докучаева)
It is shown that the profile principle of arable soils classification, implemented in the new classification of Russian soils is not correct. The separation of 2-3 new soil types in a single tilled soils was conducted only according to the presence of the arable layer. The profile of the arable soil was not analyzed. This led to serious errors, overloading of the classification by excessive, non-existent types of soils that do not carry useful information and, therefore, distorting the reality. The analysis of properties and processes in arable soils considered in the article has shown that just plowing, crops cultivation and economic activities do not change significantly the processes that formed the soil before plowing. They lead to changes of some properties in the arable soil and, however, do not reach the new natural-agrogenic horizon. Therefore, it will be correct to separate the arable soil on the level of the subtype of the soil, which was tilled. Some changes, which occurred in the properties of tilled soils are in fact new specificities superimposed on natural horizons which were created in virgin soils. Precisely this was done in the Classification and Diagnostics of Soils of the USSR (1977) during the analysis of profiles for cultivated, reclaimed and cultivated soddy-podzolic soils. However, these soils were related to the new type - the type of cultivated soddy-podzolic soils. As it is seen in the name of the soil, the genetical connection with the virgin soils was preserved. If this soil is also eroded, it will be proposed to determine the soil water erosion degree and to separate it already at the level of a type within a subtype of arable land. This could be done by the analysis of profile remains, and by using the comparative-geographic method. A new process in arable soil, which is able to form a different soil horizon, and which is not manifested only in the form of various specificities, might occur only with great efforts in soil cultivation or radical reclamation: irrigation, drainage. Only when a new horizon appears in the arable soil, according to the principles indicated in the soil classification, a new type of arable soil is separated. A significant change in the humus horizon in arable soddy-podzolic soil: its thickness, color, humus content, structure, and other properties may serve as the basis for separation of a new type - the cultivated soil type. The proposed approach will make it possible to compose a highly informative substantive-genetic classification of soils not only for natural, but also for various arable soils.